Clinical and physiological advances in sedentary behavior research - Heinonen, Ilkka (Frontiers in Physiology, 2024)
Sedentary behavior, thus sitting, has emerged as modifiable risk factor affecting our physiology and health. The evidence for detrimental effects of sedentary behavior/physical inactivity on health still however stems from epidemiological studies, which cannot address causalities. Acute and short-term sedentary behavior reduction interventions have been performed, but in these studies sitting has often been replaced by formal physical activity, thus exercise, and long-term studies in subjects with cardiometabolic risk factors are still relatively few. We have recently conducted long-term randomized controlled trial (RCT) to reduce daily sitting, without formal exercise, in metabolic syndrome patients and this mini-review presents these studies with physiological aspects. Findings indicate that sedentary behavior reduction can prevent the increase in many cardiometabolic risk factors after three-month, but more intense physical activity may be needed to reduce risk factor levels. At six-month time point reduced sitting reduced fasting insulin and successfully reducing sitting and body fat had beneficial effects also on whole-body insulin sensitivity, but other effects were relatively minor. Reduced sitting did not improve maximal aerobic fitness after 6-months, but increases in daily steps associated positively with increases in fitness. However, the more participants replaced their sitting by standing, the more their maximal aerobic fitness was reduced. Overall, while the analyses of the collected data is still ongoing, our findings suggest that the physiological and health effects of reduced sitting are relatively minor and that physical activity such as taking more daily walking steps is needed and more beneficial and time efficient for improving human health.